Nutritional Value and Antioxidant Activity of Various Extracts and Fractions of Punica granatum (Pomegranate) Peel: Nutritional Value of P. granatum Peels - Iqbal, Benish; Saeed, Muhammad Khalid; Khalid, Bushra; Liaquat, Lubna; Ahmad, Ijaz (Biological Sciences - PJSIR, 2010)
Evaluation of the nutritional value and antioxidant activity of Punica granatum peel extracts for their radical scavenging activity revealed that potent antioxidant activity, in the order of ethyl acetate fraction > chloroform fraction > petroleum ether fraction > water fraction. Ethyl acetate fraction had higher radical scavenging activity in comparison to a standard antioxidant like BHT.